2017
DOI: 10.1007/s11661-017-4258-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine-Grained Plates of Al-Mg-Si Alloy Obtained by Incremental Equal Channel Angular Pressing: Microstructure and Mechanical Properties

Abstract: In this study, an Al-Mg-Si alloy was processed using via incremental equal channel angular pressing (I-ECAP) in order to obtain homogenous, ultrafine-grained plates with low anisotropy of the mechanical properties. This was the first attempt to process an Al-Mg-Si alloy using this technique. Samples in the form of 3 mm-thick square plates were subjected to I-ECAP with the 90 deg rotation around the axis normal to the surface of the plate between passes. Samples were investigated first in their initial state, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…[ 23 ] A detailed analysis of the microstructure evolution of the material during the processing was presented in our previous work. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] A detailed analysis of the microstructure evolution of the material during the processing was presented in our previous work. [ 24 ]…”
Section: Resultsmentioning
confidence: 99%
“…Mg-0.43%wt. Si alloy is distinctly different from that in pure aluminum, with the grain rotation being more prominent than the grain subdivision due to lower stacking fault energy and the reduced mobility of full dislocations in the alloy [29,31]. Other experimental work has found that Mg and Si concentration in Al impact on the deformation mechanism and grain size in aluminum alloys [15,17,30,32].…”
Section: Resultsmentioning
confidence: 95%
“…It should be noted that such a high HAGB value is difficult to achieve by means of individual process. For instance, a single processing using mtECAP (four passes) resulted in a fraction of HAGBs of ≈40–60%, which is typical for ECAP‐based processes …”
Section: Microstructural Features Of Ufg Platesmentioning
confidence: 99%
“…Commercially, pure aluminum after eight I‐ECAP passes exhibits a homogeneous, fully equiaxial (in 3D) microstructure with an average grain size of below 1 μm and a high content of HAGBs (≈80%) . Processing the Al–Mg–Si alloy up to four passes already resulted in a grain size decrease to below 1 μm and a fraction of HAGBs of above 50% …”
Section: Microstructural Features Of Ufg Platesmentioning
confidence: 99%